Pengaruh Penempatan Karyawan, Beban Kerja, Kompensasi Terhadap Kinerja Karyawan di PT. Pionir Beton Industri - Feby Nur Janah; Hendy Tannady (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study was to determine the impact of employee placement, workload, and compensation on employee performance at PT. Industrial Concrete Pioneers. The number of samples as many as 125 respondents with purposive sampling method. IBM SPSS Statistics 20 program for multilinear regression analysis. This study uses a quantitative method through a questionnaire survey distributed from google form. The results in the study can be seen that each independent variable has a positive and significant effect on employee performance at PT. Partially Pioneer of Industrial Concrete and guidelines by conducting training and job development programs, holding a morning briefing before work to ensure and evaluate the work that has been done, reviewing employee bonuses that are in accordance with employee performance, and paying attention to enthusiasm and providing more motivation to employees to complete the task on time.